Demand control ventilation with hygro passive sensors: impact of sensor's characteristics. Issue 4 (2nd October 2019) - Faure, Xavier; Ouvrier-Bonnaz, Ophelie
Abstract: Following the increasing energy performances of building, ventilation systems are being considered as key actors in reaching both energy and indoor air quality targets. Despite several pollutants that can be used as airflow modulation inputs, French demand control ventilation for dwellings, is mainly realized using water vapour and passive sensors. A variable opening section is modulated through the relative humidity level within the room (or near the sensor). For the time being, the design step of such a system is realized using perfect systems: which means instantaneous opening variation as well as perfect modulation laws. This study aims at identifying the impact of both time delay and hysteresis on typical passive sensor devices. These elements are introduced from experimental measurements into nodal numerical models. A 4 room dwelling is considered as a test case and a step by step impact is analysed. The hysteresis is shown to have the greater impact on global extracted air flow. It leads to a conservative approach for IAQ targets but increases the energy criteria up to 6.6%.